SUMBER INFORMASI "STANDAR" DALAM CYBERSPACE - Rahartri (BACA: Jurnal Dokumentasi dan Informasi, 2012)
A library has a principal role as a place to obtain the necessary information and data needed by users. Most users need the latest information. The increasing demand of the recent information needed by user is not balanced with the availability of collections owned by the library. The limitation of collections in the library requires the librarians to dig up more necessary information from various sources in the worldwide. This makes librarians work harder to access the various sources of the information online. Many users need information about standards, while most librarians do not understand how and where they can access the information. This paper discusses the sources of the latest information standards accessible by librarians easily.